Understanding transactional sex among small scale fisherfolks in Ghana - Samuel K. K. Amponsah; Henry T. Apochie; Rachael Ackah (Marine and Fishery Sciences)
Despite its detrimental effects, transactional sex-for-fish is becoming more and more common in many African fishing states. The main objective of this study was to assess the dynamics of transactional sex among small-scale marine fisherfolk in the Axim, Apam, Dixcove, and Tema fishing communities along the coast of Ghana. Data were collected from March to May 2024 with the aid of a local facilitator through face-to-face questionnaires. Data obtained from 49 respondents covered sources of motivation, perceptions, causes, and effects of sex-for-fish transactions, and were analyzed using SPSS v27. Results showed that the majority of respondents (95.9%) acknowledged the existence of sex-for-fish transactions in these fishing communities. The primary motivations for engaging in sex-for-fish were the lack of money (34%), sexual factors (30%) and greed (18%). Main causes identified were poverty (51%), the need to pay off debt (13%), school dropout (12%) and poor parenting (12%). Major effects included death (31%), sexually transmitted diseases (22%) and teenage pregnancy (20%). Results highlight the urgent need to create credit facilities, educate the public about the harms of sex-for-fish transactions, and create alternate sources of income.